Experimental Analysis of Forced Convective Heat Transfer of Nitrate Salt in a Circular Tube at High Reynolds Numbers and Temperatures. (February 2023) - Frantz, Cathy; Buck, Reiner; Röger, Marc; Hoffschmidt, Bernhard
Highlights: A novel experimental approach using an induction heater for the evaluation of the forced convective heat transfer in tubes is proposed and validated The forced convective heat transfer of a molten nitrate salt (Solar Salt) in a circular tube is deduced experimentally for Reynolds numbers up to 220000 and for film temperatures up to 633°C A review of the literature of the thermophysical properties of Solar and the forced convective heat transfer of molten salts in circular smooth tubes is provided Abstract: The forced convective heat transfer of molten nitrate salt in a circular smooth tube is experimentally investigated using a water-cooled induction heater. This novel setup is first validated using water as the main fluid, as its heat transfer is well-known. To enable an accurate deduction of the Nusselt number, a detailed review on the state-of-the-art of the thermophysical properties of Solar Salt is provided. The final experiments are carried out with "Solar Salt" at fluid bulk temperature ranging between 300°C and 550°C. The salt mass flow is varied in order to cover Reynolds numbers ranging from 14000 up to 220000. Furthermore, the experiments are conducted for different heat fluxes ranging from 330 kW/m² up to 920 kW/m². This paper provides data on the behavior of the forced convective heat transfer of molten salt for Reynolds numbers larger than 100000. To investigate the impact of local overheating of the salt above its chemical stability limit (i.e. 600°C), the mean Nusselt number is evaluated for inner wall temperatures up to 633°C. Mean Nusselt numbers are reported and compared to the well-known Gnielinski correlation.